Effect of soil contaminated by diesel oil on the germination of seeds and the growth of Schinus terebinthifolius Raddi (Anacardiaceae) Seedlings - Cleusa Bona; Igor Mendonça de Rezende; Gedir de Oliveira Santos; Luiz Antônio de Souza (Brazilian Archives of Biology and Technology, 2011)
The effect of soil polluted by diesel oil on the germination of seeds and the growth of Schinus terebinthifolius Raddi seedlings was analyzed at different times after contamination of the soil. The experiments were conducted under greenhouse conditions, with four treatments and five repetitions. The four treatments included: soil contaminated 30 (T30), 90 (T90) or 180 (T180) days before planting as well as a non-polluted soil (T0) (control). Soil saturated to 50% of its maximum retention capacity (MRC) was contaminated with diesel oil at a rate of 92.4 mL per kg. The germination rate and germination speed index (GSI) were significantly affected only in T30. The development of the plants was affected significantly in all the treatments, with reductions of biomass and eophyll area. It could be concluded that diesel oil significantly affected the germination, GSI and seedling growth of S. terebinthifolius, but the toxic effect decreased over the time.